A review of nanogrid topologies and technologies. (January 2017) - Burmester, Daniel; Rayudu, Ramesh; Seah, Winston; Akinyele, Daniel
Abstract: The centralised power grid bears a heavy burden in a time when consumers expect an uninterrupted reliable power supply, a reduction in carbon emissions, increased efficiency within the national grid and power supplied to remote communities. As expectations increase, it becomes the task of power systems research and design to develop new structures to meet these demands. This has led to alternatives being sought for centralised power generation, which is prone to outages (due to long distance transmission), is a substantial contributor to global carbon emissions, has large transmission losses and is often not a practical solution when supplying remote communities. Distributed generation (DG) looks to remedy these inadequacies by producing power close to its point of consumption, often utilising carbon neutral, renewable energy (RE) sources (sun, wind). To maximise the efficient use of DG, control structures are used to balance the intermittent RE power production with consumer power consumption. One such structure is used to implement control of small scale DG, at a single house/small building level: the nanogrid. This paper explores the current nanogrid research, it collates the existing definitions and uses the knowledge to give a concise definition of a nanogrid. It then discusses the control topologies and techniques which enable the intelligent control of the nanogrid, before presenting the hardware platform used to ensure the efficient operation of a small scale DG system. The paper then considers the interconnection of multiple nanogrids forming a network (microgrid), facilitating the sharing of power between individual nanogrids. The future developments are then explored before the paper's conclusions are presented.